The Influence of Glycerol Monostearate Concentration and Storage Condition on Tomato Powder’s Contents Using Foam Mat Drying Method - Putri Ramadhany; Abigail Fern Pramana; Arabella Febiola; Tony Handoko (Dept. of Chemical Engineering, Diponegoro University, 2021)
Tomato is a seasonal horticultural product that has beneficial effects on human health. It contains a high concentration of lycopene and vitamin C. However, tomato production, which continues to increase in Indonesia, is not balanced with its consumption. Due to its high moisture content, harvested tomato relatively has a short shelf-life. Resultantly, the unconsumed tomato will end up being wasted. One way to prolong tomato’s shelf-life is by converting it into powder form. In this research, the tomato was shifted into tomato powder using a foam mat drying method. The weight ratio of GMS to tomato juice was varied: (1) 4%-w/w, (2) 5%-w/w, and (3) 6%-w/w. Tomato powder was then stored in two types of materials (sealed brown glass bottle and laminated aluminium foil (LAF) resealable zipper) and three conditions (refrigerator ( ± 4 ℃), room temperature (± 25.2 ℃) and sun-exposed (± 30 ℃)). According to the results, foam mat drying could maintain the nutrients of the tomato powder. Increasing GMS larger than 5%-w/w had no big impact on reserving lycopene and vitamin C. At 5%-w/w GMS, tomato powder consisted of 1.09%/w/w moisture, 42.58 mg/100 g lycopene, and 123.28 mg/100 g vitamin C. It was found that moisture and vitamin C on tomato powder content was influenced by storage conditions, while lycopene content was influenced by storage material. Moisture content and vitamin C were best maintained at the sun-exposed condition and room temperature, respectively. While lycopene was best stored in the laminated aluminium foil (LAF) resealable zipper.